Pengaruh Fly Ash Dan Bottom Ash Sebagai Bahan Substitusi Pada Beton - Marlyana Antika Pagau; Jonie Tanijaya; Desi Sandy (Paulus Civil Engineering Journal, 2020)
Generally, factory waste cannot be disposed of directly because it can pollute the environment. In the city of Makassar, South Sulawesi, to be precise at PT. Makassar Tene uses coal as factory fuel, where the rest of the coal combustion produces fly ash and bottom ash waste which requires processing before disposal. This study aims to determine the value of compressive strength, split tensile strength and flexural strength of concrete and to determine the effect of the percentage of fly ash and bottom ash substitution in the concrete mixture. This research was conducted using the American Concrete Institute (ACI) method with a design quality of 23 MPa. Based on this research, it can be seen that the concrete mixture with fly ash and bottom ash substitution causes the concrete to experience a decrease in strength as the percentage of bottom ash substitution increases.